Perubahan Pola Belajar Siswa akibat Dominasi Teknologi Digital: Kajian Literatur - Nabilah Nurjannah; Rizki Maulana; Muhammad Chepy Revy; Hana Kamilah; Abdul Fadhil (Advances In Education Journal, 2026)
The rapid development of digital technology has significantly changed students' learning patterns through the widespread use of the internet, Artificial Intelligence (AI), social media, and digital learning platforms. This study aims to analyze these changes, identify their impacts, and examine strategies for optimizing technology in learning. A literature review method was employed by analyzing relevant journal articles and other academic sources. The results indicate that digital technology has shifted learning from teacher-centered to student-centered approaches, increasing students' independence, flexibility, and access to diverse learning resources. However, excessive reliance on digital technology may lead to gadget addiction, learning distractions, misuse of AI, and reduced face-to-face social interaction. The study concludes that strengthening digital literacy, enhancing the roles of teachers and parents, and implementing adaptive learning strategies are essential to maximize the benefits of digital technology while minimizing its negative impacts on students' learning.